CLOSE-UP OF THE END-PERMIAN MASS EXTINCTION HORIZON RECORDED IN THE MEISHAN SECTION, SOUTH CHINA: SEDIMENTARY, ELEMENTAL, AND BIOTIC CHARACTERIZATION AND A NEGATIVE SHIFT OF SULFATE SULFUR ISOTOPE RATIO - Kaiho K.; Chen Z.-Q.; Kawahata H.; Sato H.; Kajiwara Y. (My University, 2006)
The Permian/Triassic (P/Tr) boundary beds of the Meishan section, South China, have been re-studied in detail based on complete samples across the P/Tr transition. Under the microscope, the end-Permian mass extinction horizon is calibrated to a 12-mm stratal interval, the top being 19 mm below the top of Bed 24e of the Changhsing Formation. This abrupt disappearance of skeletal fragments of major benthos characterizes the end-Permian extinction event, suggesting a catastrophic event. An abrupt decrease in the 34S/32S ratios of seawater sulfate is confirmed to coincide with the end-Permian event horizon. The sulfur isotope event is thought to have been caused by an overturn of a stratified ocean dominated by H2S, implying coincidence of the oceanic mixing and the mass extinction. Coincident Siberian flood volcanism may have triggered a long-term (> 103 years) cooling leading an ocean mixing. A presumed comet impact to the ocean could have directly caused ocean mixing and the mass extinction. © 2006 Elsevier B.V. All rights reserved.
Keywords: ELEMENT; FOSSIL; MASS EXTINCTION; PERMIAN; S-34/S-32; TRIASSIC; Paleozoic::Permian; Палеозой::Пермская